2009
DOI: 10.1593/neo.09506
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Influx and Chemokine Production during the Early Phases of the Antitumor Response to the Vascular Disrupting Agent DMXAA (ASA404)

Abstract: 5,6-Dimethylxanthenone-4-acetic acid (DMXAA) acts through tumor vascular disruption and cytokine production and is the first of its class to enter phase 3 trials. We characterized leukocytes and cytokines in murine Colon 38 tumors before and after DMXAA treatment. Tumor mass declined 50% 24 hours after DMXAA administration, but the leukocyte count per gram of tumor increased threefold owing to a large influx of Ly6G(+)CD11b(+)F4/80(-) cells with the morphology of neutrophils. However, B and T lymphocytes, natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 24 publications
5
47
0
Order By: Relevance
“…Based on our findings, we suggest that hypericin is partially cleared from necrotic tissue by uptake in polymorphonuclear neutrophils, and it seems unlikely that this phenomenon makes up part of an immunologically concerted mechanism. Furthermore, this theory is in line with previous findings that neutrophil levels in subcutaneously implanted Colon 38 tumors are increased shortly after DMXAA treatment (Wang et al 2009). …”
Section: Discussionsupporting
confidence: 92%
“…Based on our findings, we suggest that hypericin is partially cleared from necrotic tissue by uptake in polymorphonuclear neutrophils, and it seems unlikely that this phenomenon makes up part of an immunologically concerted mechanism. Furthermore, this theory is in line with previous findings that neutrophil levels in subcutaneously implanted Colon 38 tumors are increased shortly after DMXAA treatment (Wang et al 2009). …”
Section: Discussionsupporting
confidence: 92%
“…The results (shown in Supplementary Fig. 6 ) were consistent with DMXAA exerting its antivascular activity through cytokine induction and chemokine modulation, including induction of tumor necrosis factor (TNF-alpha) and interleukin (IL-6) canonical pathways (28-30). Analysis of the functional interactions between gene classes in the transcriptomes under study with Gene Ontology identified several annotated biomarkers including IL-8, MMP-10, STAT1, STC1, FSTL3, CXCL1 and CTSB.…”
Section: Resultssupporting
confidence: 77%
“…This effect has been detected within 30 minutes of administration in animal models (Figure 5). 80,81 A large and early influx of neutrophils into subcutaneous Colon 38 tumors occurs following ASA404 treatment, and neutrophils have therefore been suggested as mediators of the drug’s rapid anti-vascular effects 82. Activated neutrophils are strongly implicated in endothelial cell damage and killing during inflammation 83.…”
Section: Classes Of Tumor-vdas and Their Mechanisms Of Actionmentioning
confidence: 99%